What Do We Know About Ise Literature? A Bibliometric Review - Rahmat, Rahmat; Nurjannah, Mauliya Redyan (Universitas Siliwangi, 2025)
Purpose/Objective Study: This study aims to analyze publication trends on Islamic Social Enterprise (ISE) using bibliometric analysis.Design/Methodology/Approach: The method used is a literature review with a bibliometric analysis approach using R Studio software. In this study, there are six subthemes discussed, namely trends in the number of publications, number of citations, countries, journal publications, research collaborations, researcher affiliations, and future research topics.Findings: The analysis showed that an average of 4.73% of papers were published annually; the number of citations from 1979-2004 was only about 0.2%, while from 2005-2023 it reached 2%. Malaysia and Indonesia are the countries that conduct the most research on ISE. ISE journal publications are dominated by several international journals, and research collaborations and researcher affiliations are dominated by universities from both countries. Future ISE research topics are still limited, with potential keywords such as Social Enterprise, Islamic Social Enterprise, and Small and Medium Enterprises.Type Paper: Article review